OpenLISEM Flash Flood Modelling Application in Logung Sub-Catchment, Central Java - Fitrie Atviana Nurritasari; Sudibyakto Sudibyakto; Victor G. Jetten (Faculty of Geography, Universitas Gadjah Mada, 2015)
Juwana Catchment and Logung Sub-catchment in particular has been suffering several major past flood events with significant loss. This study conducted an assessment of flood risk by using OpenLISEM as physical soil and hydrological model to generate the single storm flash flood occurrences. The physical input data were collected from remote sensing image interpretation, field observation and measurement and literature review. There are three return periods chosen as scenarios that represent rainfall intensity in Logung Sub-Catchment. Model validation was done by adjusting initial moisture content and saturated hydraulic conductivity values to equate the calculated total discharge with the measured total discharge in several chosen dates. The results show increases in most of modeled hydrological parameter with respect to increasing of rainfall intensity.